Aking Rice Flour Giving To Carcass Cracks Of Super Native Chickens Aged 10 Weeks - I Gede Andre Ekayana; I Gst Agus Maha Putra Sanjaya; Ni Made Yudiastari (Warmadewa University Press, 2024)
The livestock sector plays a real role in national food security through the provision of animal protein, especially in the poultry sector, becoming one of the business fields that many Indonesians look at, one of which is raising super native chickens. Super native chickens need quality feed for nutritional fulfillment in order to get optimal results. But the reality faced by farmers today is that the price of commercial feed on the market is very expensive. Feed ingredients that need to be used as alternative feed ingredients are aking rice. The purpose of this study was to determine the effect of giving aking rice flour in the ration on the carcass cracking of super kampong chickens aged 10 weeks. The experimental design used was a Complete Randomized Design (RAL) consisting of 5 treatments and 3 repeats. The treatment is N0 (ration without the addition of aking rice flour), N1 (ration containing 5% aking rice flour), N2 (ration containing 10% aking rice flour), N3 (ration containing 15% aking rice flour ), N4 (ration containing 20% aking rice flour). The results showed that the addition of aking rice flour in the ration had an intangible effect (P>0.05) on the variables of carcass weight, chest weight, thigh weight, and back weight. While the variable wing weight shows a noticeable influence (P<0.05). Giving aking rice flour with a level of 10% (N2) in the super native chicken ration gave the highest results on the variables of carcass weight, breast weight, pada weight, and back weight, while on the wing weight variable showed the highest value in treatment with a level of 15% (N3). So it can be suggested that the provision of aking rice flour in the ration of super kampong chickens can still be tolerated up to the level of 15%.